Agent most wanted : the never-before-told story of the most dangerous spy of World War II - Purnell, Sonia (Viking, 2022)
Profiles the life of Virginia Hall, a socialite, who became the first Allied woman in WWII to be sent behind enemy lines. Despite her prosthetic leg, she helped establish spy networks throughout France, and even when her cover was blown, she refused orders to evacuate. Though she finally escaped France, she went back, saying that she had more lives to save. Includes black-and-white photographs.